TOWARDS A TRADE POLICY FOR DEVELOPMENT: THE POLITICAL ECONOMY OF SOUTH AFRICA'S EXTERNAL TRADE, 1994-2014 (The Strategic Review for Southern Africa, 2020)
Over the past 20 years of democracy, there has been a strategic reorientation of South Africa's trade policy. In the early 1990s, the post-apartheid state undertook extensive tariff reform, driven by its multilateral and regional commitments, as well as unilateral liberalisation consistent with the austere macro-economic agenda of the time. By the second decade of democracy, an institutionalised industrial policy designed to strengthen and diversify South Africa's productive capabilities had come to determine and shape South Africa's external trade agenda and negotiations. This more strategic trade policy orientation has required the preservation and expansion of policy space in bilateral, regional and multilateral agreements, and more novel approaches to South-South economic cooperation. There was also a fundamental shift in thinking on regional integration away from a conventional market-led model premised on the European Union's experience, to a 'developmental integration' approach that concurrently prioritises market integration, infrastructure development and structural economic transformation. This article critically reviews how South Africa's trade policy and negotiating agenda have been recalibrated as instruments of industrial policy over the two post-apartheid decades. The article concludes with some observations about the future direction of South Africa's trade agenda during the third decade of democracy.